ANALISIS SISTEM INFORMASI AKUNTANSI KREDIT PEGAWAI NEGERI SIPIL PADA PT. BANK JATIM CABANG NGANJUK - GITA PURI, ADITYA Gita (Jurnal Akuntansi AKUNESA, 2012)
Credit is money supply based on engagement between customer (debitor) and bank with any party that should be paid with any condition term and interest and also penalty if the customer was late for installment payment. Purposing a credit proposal from debitor to the bank with any condition of their salary is called credit of civil servants for consumption, investment or additional working capital. These research used case study analysis on Bank Jatim. These research’s purpose is for analyzing and informing anyone about the legitimation and how the procedure of purposing credit of civil servants.Keywords: Credit, Credit of Civil Servants, Bank, Accounting Information system